2001
DOI: 10.1002/1521-3765(20010702)7:13<2848::aid-chem2848>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene–Cyclam: A Redox-Active Macrocycle for the Complexation of Transition Metal Ions and a Study on the Influence of the Relative Permittivity on the Coulombic Interaction between Metal Cations

Abstract: The reaction of 1,1'-ferrocene-bis(methylenepyridinium) salt with 1,4,8,11-tetraazacyclotetradecane-5,12-dione, followed by LiAlH4 reduction results in the formation of FcCyclam. Metal complexes of FcCyclam with M2+ = Co2+, Ni2+, Cu2+, and Zn2+ were synthesized from FcCyclam and the respective metal triflates. The complexation of Cu2+ and FcCyclam in CH3CN is preceeded by a rapid electron transfer, followed by a slower complex formation reaction and a reverse electron transfer. The protonation constants of FcC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 35 publications
2
43
2
Order By: Relevance
“…In recent years, there has been an interest in the electrochemical detection of ion binding to a ligand which is equipped with a redox active group, such as ferrocene (Fc) or cobaltocene [1][2][3][4][5][6][7][8][9][10][11]. The specificity of the system is dictated by the ligand-ion interactions and detection sensitivity depends on the efficiency of the electronic communication between the ligand-ion complex and the redox group, either through-space or through-bond.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In recent years, there has been an interest in the electrochemical detection of ion binding to a ligand which is equipped with a redox active group, such as ferrocene (Fc) or cobaltocene [1][2][3][4][5][6][7][8][9][10][11]. The specificity of the system is dictated by the ligand-ion interactions and detection sensitivity depends on the efficiency of the electronic communication between the ligand-ion complex and the redox group, either through-space or through-bond.…”
Section: Introductionmentioning
confidence: 96%
“…The specificity of the system is dictated by the ligand-ion interactions and detection sensitivity depends on the efficiency of the electronic communication between the ligand-ion complex and the redox group, either through-space or through-bond. Various Fc substituted macrocycles such as cyclams [2], cryptands [1,3], aza-crowns [4], crown ethers [12], and calixarenes [9] have been shown to electrochemically sense the coordination of alkaline-, alkaline earth-, transition-metals and lanthanide ions. Furthermore, peptides are known to show specificity towards metal binding, as was determined by titration experiments using NMR [5][6][7], potentiometry [11], luminescence measurements [8] FT-IR, CD and UV-vis spectroscopy [10].…”
Section: Introductionmentioning
confidence: 99%
“…The design and synthesis of macropolycyclic receptors incorporating ligating heteroatoms are actively pursued for the development of functional nanodevices. [2][3][4][5] Selective molecular recognition 6,7 and signalling [8][9][10][11][12] properties are sought to provide the major impetus for further progress in this flourishing area of chemistry, while various applications in biochemistry and medicine, catalysis, or material sciences have already opened new horizons for the utilization of this class of compounds. [13][14][15][16][17] In this respect, conformationally constrained bicyclic polyamines with bridgehead nitrogen atoms have gained increasing attention over the last three decades because the additional rigidity provided by strapping the macrocyclic framework imparts intriguing anion- 18 and metal-binding properties.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 In contrast, amide-containing azamacrobicyclic ligands have attracted much less attention, 37 although they provide a convenient access to strapped cyclen or cyclam derivatives upon reduction of the protecting carbonyl groups. 8,9,[38][39][40][41] From a synthetic point of view, trans-dioxocyclam (5,12-dioxocyclam or 1,4,8,11-tetraazacyclotetradecane-5,12-dione, compound 1 in Scheme 1) 42,43 is an attractive starting material since two out of the four secondary amines of the 14-membered ring, namely those located in positions 4 and 11, take part in two peptidic bonds and thus are masked. Optically active C-functionalized analogs, obtained by photolysis of chromium carbene complexes in the presence of suitable imidazolines, have been described more recently by Hegedus and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the insertion of a transition metal ion into the macrocyclic cavity may lead to enhanced recognition properties. Previous studies have shown that ferrocenyl-substituted polyazamacrocycles are good candidates for the electrochemical recognition of anions [13,[18][19][20][21][22][23][24]. In this paper, we present a new series of ferrocenyl ionophores, L 1 , L 2 , L 3 and L 1 Cu, (Scheme 1) designed for anionic sensing.…”
Section: Introductionmentioning
confidence: 99%